Technological aspects and requirements to raw materials for increasing the nutritional value of glaze - E. V. Mazukabzova (Пищевые системы)
Glaze, giving confectionery products an aesthetically attractive appearance, provides the possibility of prolonging their shelf life. The main raw components of the glaze are sugar and fat, which determines its high caloric content. Modern trends dictate the need to create confectionery products enriched with essential nutrients found in vegetables, berries and fruits. The introduction of finely ground additives in the form of fruit and vegetable powder into the glaze formulation may entail changes in the rheological and crystallization properties of the glaze. The aim of the research is to develop technological methods of fruit and vegetable confectionery glaze production with increased content of dietary fibers and reduced amount of added sugar, as well as to establish requirements for fruit and vegetable powders as raw materials used in the production of confectionery glaze. The objects of the research were industrial samples of fruit and vegetable powders from raspberry, apple, carrot and beet, as well as samples of confectionery glaze produced in laboratory conditions. Common and special research methods were used in the work. The technological acceptability of using fruit and vegetable powders in the production of confectionery glaze according to their physical and chemical parameters has been determined. The yield stress of the glaze increased as the content of fruit and vegetable powder increased from 3 to 15% to varying degrees depending on its fat-absorbing capacity. The crystallization characteristic of the glaze changed: the solidification temperature decreased by 1-2 °C, the crystallization duration increased by 27-40% compared to the control sample. The nomenclature is substantiated and numerical values of quality criteria of fruit and vegetable powders to ensure technological properties of glaze are given. The influence of step-by-step introduction of surfactants on the value of yield stress of confectionery glazes with fruit and vegetable powders is shown. The technology of fruit and vegetable confectionery glaze with a high content of dietary fiber (9 g/100 g) and with a reduced amount of added sugar has been developed.